Management efficacy in a metapopulation model of white‐nose syndrome. (6th April 2021) - Duan, Junyan; Malakhov, Mykhaylo M.; Pellett, Jordan J.; Phadke, Ishan S.; Barber, Jackson; Blackwood, Julie C.
Abstract: The fungal pathogen Pseudogymnoascus destructans ( Pd ) causes white‐nose syndrome (WNS), an emerging disease that affects North American bat populations during hibernation. Pd has rapidly spread throughout much of the continent, leading to mass mortality and threatening extinction in several bat species. While previous studies have proposed treatment methods, little is known about the impact of metapopulation dynamics on these interventions. We investigate how the movement of bats between populations could affect the success of five WNS control strategies by posing and analyzing a two‐population disease model. Our results demonstrate that vaccination will benefit from greater bat dispersal, but the effectiveness of treatments targeting fungal growth or disease progression can be expected to diminish. We confirm that successful control depends on the relative contributions of bat‐to‐bat and environment‐to‐bat contact to Pd transmission, and additionally find that the route of transmission can influence whether interpopulation exchange increases or decreases control efficacy. Recommendations for Resource Managers 1. Many WNS controls are under development, but an analysis of host dynamics is needed to select the most effective management strategies. 2. Our study indicates that the long‐term efficacy of control strategies depends on the presence and magnitude of interpopulation movement, and highlights the importance of quantifying bat metapopulation dynamics together with the avenues of Pd transmission. 3. We suggest that movement between populations suppresses the efficacy of most interventions and recommend managers to consider both their combination of control strategies and the primary route of pathogen transmission when evaluating the potential impacts of dispersal. 4. Vaccination was the only intervention strategy to consistently benefit from bat dispersal so, if possible, we advocate for the development and widespread administration of a WNS vaccine.